Microencapsulation: A technological alternative to preserve active ingredients in functional foods - BERRÍO ESCOBAR, Jhon Fernando; MÁRQUEZ FERNÁNDEZ, Diana Margarita (Vitae, 2018)
In the late 80’s started the rise of researches related to the obtainment of food capable of supplying the energetic demand, promoting growth and encompassing better properties and benefits for the human being. Due to their nutritional and pharmacological features, these foods were called nutraceutical or functional foods as they comprise one or more components, not necessarily nutrients, that promote health, prevent diseases and strengthen the immune system or exhibit medical properties. Regardless such researches increase and despite the approval for use and commercialization of these foods, in most countries there is neither a statutory definition nor any specific legislation that governs them.